Imaginaries and Rhythms of Remoteness - Tatiana Bajuk Senčar (Svetovi, 2025)
This article presents an examination of the mutually constitutive relationship between remoteness and connectivity in the alpine tourist destination of Bohinj in Slovenia. Building upon existing ethnographic explorations of remoteness and tourism imaginaries, the author explores how the alpine locality of Bohinj has been continually made and remade as an out-of-the-way tourist destination and how the imaginary of remoteness presents itself in everyday life, which is analysed through the lens of tourism seasonality.